The perception of smallholders towards roles and challenges of RSPO implementation at Felda Tun Ghaffar Kemendor and Felda Tun Ghaffar Ayer Kangkung, Melaka / Abu Bakar Hasan - Hasan, Abu Bakar (Faculty of Plantation and Agrotechnology, 2017)
Roundtable on Sustainable Palm Oil (RSPO) is the organization responsible in controlling, monitoring and evaluating economic, social and environmental impacts of the production and uptake of Crude Sustainable Palm Oil (CSPO). However, from the side of oil palm smallholders, there are several barriers faced by them in implementing the principle and criteria set by RSPO efficiently. Thus, this survey is conducted based on two main objectives which are to examine the relationship of smallholders’ perception about roles of RSPO and challenges of its implementation. Next is to assess the most influential factor towards RSPO implementation through smallholders’ perception. This survey is conducted by distributing questionnaires to the oil palm smallholders around 87 persons which are randomly selected. Generally, there are two types of independent variables that are included in this survey which are the roles of RSPO agency itself besides the challenges in implementing the RSPO standard focusing towards the smallholders. Concept of 3P which are People, Profit and Planet are under the roles variable while cost besides training and guidance for smallholders are under challenges of RSPO implementation. The data collected after survey process is analysed using Statistical Package for Social Science (SPSS) in order to obtain result for descriptive analysis, demographic study, correlation and also regression. Through the analysis process, all the elements of roles and challenges have a positive linear correlation with RSPO implementation. As for regression analysis, the training and guidance shows highest coefficient reading with value of 0.492 for the challenges aspect. Besides, the analysis showed that around 30.9% of variation in RSPO implementation is explained by roles and challenges elements. Based on the result analysed in this study, it is clearly shown that the factor of training and guidance has becomes the most crucial factor among the independent variables. The other two factors which are concept 3P and cost do not greatly affect the RSPO implementation if compared to the factor of training and guidance. For the recommendation, there are much more things should be done for oil palm smallholders. For examples, more researches, supports and scaling up of viable models are required to guarantee that smallholders are not left behind. Besides, RSPO and government should provide and plan more financial assistance for smallholders compared to bigger plantation companies as the process of implementing the regulation of RSPO is costly for the smallholders. Furthermore, the related authorities should increasing collaboration with private plantation companies in providing training and guidance for the smallholders.